The Clinical Profile of Oral Lichen Planus - Shah, Syed Murad Ali; Ilyas, Muhammad; Kundi, Jawad Ahmad (Journal of Gandhara Medical and Dental Science, 2016)
OBJECTIVES The objective of the study was to determine the clinical profile of oral lichen planus. METHODOLOGY This retrospective cohort study was carried from January 2011 to December 2015 at the Department of Oral and Maxillofacial Surgery, Sardar Begum Dental College, Peshawar.A total of 36 with 14 male and 22 female patients having oral lichen planus from were selected. On defined and population-based sample the age selected was ≥ 20 years and divided into four categories i.e..,20-29 years,30-39 years,40-49 years and 50-59 years. The diagnostic criteria proposed by van der Meij et al 23 in 2003 based on the WHO definition of oral lichen planus were used to identify the cases of oral lichen planus.That entire patient’s with incomplete records and aged > 60 years were excluded. The data was analyzed through SPSS 22 at the significance level of p < 0.05 and Chi-square statistics was applied for site and gender association. RESULTS The mean age presentation was 39.2 (SD± 15.49) years. The female to male ratio was 1:57:1. The dominant aged group was 30-39 years with n=16 (44.44%).The buccal mucosa was the most common site involved n=28(77.8%).Reticular type of oral lichen planus was the most common form and was present in n=22(61.1%) patients however, bilaterally involved mucosa was commonly seen. Chi-square statistics showed a significant association between bilateral involvement of oral mucosa in oral lichen planus with both male and female (x2= 5.833, p= 0.016). CONCLUSION The most common site involved in oral lichen planus was buccal mucosa, most common form was atrophic with female predominance and bilaterally involved oral mucosa was significantly associated with gender.